Case Report: Ictal Central Apnea as First and Overlooked Symptom in Temporal Lobe Seizures - Micalizzi, Elisa; Vaudano, Anna Elisabetta; Giovannini, Giada; Turchi, Giulia; Giunta, Leandra; Meletti, Stefano (Frontiers in Neurology, 2021)
Ictal respiratory changes have been mainly described following generalized tonic-clonic seizures and recently considered to be a biomarker to assess the risk of sudden unexplained death in epilepsy (SUDEP). Nonetheless, modification of respiratory pattern can be related also to focal seizures, especially arising from the temporal lobe. Changes in cardiac function such as tachycardia or bradycardia could be often associated. We report a short case series of four patients with temporal lobe epilepsy admitted to our Epilepsy Monitoring Unit (EMU) presenting with an ictal central apnea as the first clinical manifestation of their seizures. None of these patients was aware of the occurrence of respiratory arrest. Age at onset ranged from 15 to 29 years. One patient had seizures with prolonged central apnea accompanied by a significant decrease in oxygen saturation. Neuroimaging in two patients showed alterations of mesial temporal lobe structures, including the amygdala. Recent neurophysiological studies supported the existence of a cortical network involving the limbic system that modulates downstream brainstem respiratory centers. Monitoring for respiratory changes and oxygen saturation in focal seizures is warranted for their potential value in identifying the epileptogenic zone and for a better understanding of ictal respiratory changes that could potentially define a subgroup of patients with high risk of seizure-related autonomic changes.